Promoção da argumentação por meio de um minicurso sobre astrofísica estelar para alunos do 9º ano do ensino fundamental ao 3º ano do ensino médio - Eufrásio, Dayvidson Siqueira (2022)
This paper presents the proposal of a short course on stellar astrophysics, specifically the study of the birth, life, and death of stars, and the results achieved when developed with basic education students. The purpose of the course was to contemplate students from the ninth year of Elementary School to the third year of High School; its full preparation was designed to be carried out in person. Due to the Covid-19 pandemic period, its development took place remotely with videos and texts on the subject as didactic resources for autonomous studies; the teacher assumed the mediator role in the proposed activities. When carrying out this proposal, the students answered questionnaires with data from this research, in addition to the studies, and argumentation elements were identified in the answers, indicating the favoring of scientific literacy promoted by the short course. The analyzes carried out indicate that the short course presents favorable conditions to urge arguments during its development, favoring the basic understanding of fundamental scientific terms, knowledge, and concepts, relevant aspects to promote the students' scientific literacy.